Chrysotile asbestos upregulates gene expression and production of alpha-receptors for platelet-derived growth factor (PDGF-AA) on rat lung fibroblasts. - Bonner, J C (1993)
PDGF isoforms have been postulated to serve as mediators of fibroblast proliferation and chemotaxis during lung fibrogenesis induced by asbestos inhalation. We have studied the interaction of chrysotile asbestos fibers with rat lung fibroblasts (RLF) in vitro and the consequent changes in PDGF receptor mRNA expression, PDGF binding, and mitogenic activity of PDGF isoforms. Northern blot analysis revealed that mRNA for the PDGF-receptor alpha subtype (PDGF-R alpha) on RLF was upregulated after a 24-h exposure to asbestos in culture (0.5-15 micrograms fibers/cm2). [125I]PDGF-BB receptor assays showed that normal RLF possess mainly PDGF-R beta and a paucity of PDGF-R alpha. In agreement with the Northern data, saturation binding of [125I]PDGF-BB to RLF exposed to asbestos demonstrated an approximately 40% increase in binding sites accompanied by a twofold decrease in receptor affinity. Treating asbestos-exposed RLF with PDGF-AA, which binds only PDGF-R alpha, blocked the PDGF binding sites that were upregulated by fiber exposure. PDGF-AA had increased mitogenic potency for fiber-exposed RLF, but PDGF-BB was a less potent mitogen for these RLF. Nonfibrogenic carbonyl iron spheres induced similar changes in PDGF growth responses. These data show that inorganic particulates alter the PDGF-R alpha population on RLF without significant change in PDGF-R beta.